Bullying In the Perspective of Indonesian Law, Islamic Law, And Human Rights: (Case Study: Timothy's Bullying) - Raden Bagus Muhammad Aji Bagaskoro Meliala; Sarkowi; Heru Rohmansjah; Gregorius Cristison Bertholomeus; Dani Amran Hakim (Yayasan Inovasi Kemajuan Intelektual, 2025)
Bullying has transformed from a mere school behavior problem into a serious human rights violation with complex legal implications. This study aims to analyze the phenomenon of bullying through three normative lenses: Indonesian positive law, Islamic law, and international human rights instruments, with a particular focus on the case study of Timothy. The research method used is a normative juridical approach with a case study. The results show that Indonesian law, through the Child Protection Law, has provided criminal sanctions, but its implementation is still hampered by diversion for child perpetrators. From an Islamic legal perspective, bullying is considered an act of injustice that violates the principles of hifdz al-nafs (protection of life) and hifdz al-'ird (protection of honor). Meanwhile, a human rights perspective views bullying as a violation of the right to security and human dignity. Timothy's case underscores the need to synchronize preventive and repressive policies that are more humane yet still deter. This study recommends strengthening religion-based character education and strict supervision of children's social environments.